2014
DOI: 10.1111/1467-8551.12072
|View full text |Cite
|
Sign up to set email alerts
|

Double Trouble: Sibling Rivalry and Twin Organizations in the 2008 Credit Crisis

Abstract: The purpose of this article is to introduce and explore the novel idea of highly similar 'twin organizations'. Drawing on psychoanalytic theory in my formulation, I argue that the closeness of organizational identities in twin organizations may lead to increased rivalry, narcissism and a tendency for greater risk-taking and vulnerability. Four of the biggest casualties of the 2008 credit crisis -two UK banks (HBOS and RBS) and two large US financial institutions (Fannie Mae and Freddie Mac) -are used to illust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
4
0
2
Order By: Relevance
“…The period between 2006 and 2011 was chosen since the recent global financial crisis spanned these years, in which 2008 was the most unprofitable year recorded by the companies in the data set where the lowest negative means of annual return on equity ROE were shown (data available upon request). Consequently, the hypothesis testing using the context of the observed years would reflect the time factor related to this credit crisis (Stein, 2015).…”
Section: Research Methods 31 Contextmentioning
confidence: 99%
“…The period between 2006 and 2011 was chosen since the recent global financial crisis spanned these years, in which 2008 was the most unprofitable year recorded by the companies in the data set where the lowest negative means of annual return on equity ROE were shown (data available upon request). Consequently, the hypothesis testing using the context of the observed years would reflect the time factor related to this credit crisis (Stein, 2015).…”
Section: Research Methods 31 Contextmentioning
confidence: 99%
“…Building on the importance of leaders, and applying the theoretical lens of psychoanalysis of sibling and twin rivalry (Burlingham, 1949(Burlingham, , 1963 to the study organizational dynamics (Brown, 1997;Clancy, Vince and Gabriel, 2012), Stein (2015) examined two pairs of twin firms: Halifax Bank of Scotland and Royal Bank of Scotland and Fannie Mae and Freddie Mac from the US and analysed why do some firms continue to get into difficulty and fail. Set in the context of the 2008 Global Financial crisis period, Stein found that the rivalry between twin firms operating in a business culture that is fuelled by greed and mania are more prone to failure due to the narcissistic behaviours by leaders of such twin organizations.…”
Section: Microlevel Influencesmentioning
confidence: 99%
“…Možemo zaključiti da je ravnatelj ključni čimbenik kvalitete i uspješnosti škole. Školski ravnatelji moraju razumjeti srž ljudske prirode i što motivira ljude, snažno baratati suradničkim međusobnim odnosima, te trebaju razumjeti razliku između različitih participativnih, direktivnih i autokratskih stilova vođenja (Stein, 2015). U Republici Hrvatskoj osnivač obrazovnih ustanova je Ministarstvo znanosti, obrazovanja i športa i županije.…”
Section: Uvodunclassified